2006
DOI: 10.1002/jso.20456
|View full text |Cite
|
Sign up to set email alerts
|

The risk of developing metastatic disease in colorectal cancer is related to CD105-positive vessel count

Abstract: The assessment of tumor angiogenesis with anti-CD105 was not sufficient for its use as a surrogate end point for survival because of the amount of survival variability explained was only 8% in absence of metastatic disease. In contrast, multivariate logistic regression analysis revealed that CD105-vessels count can identify patients at high risk of metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 44 publications
2
39
1
Order By: Relevance
“…The levels of endoglin obtained with the commercial ELISA kit were greater than those reported by Li [16], who used an indirect sandwich ELISA kit. At the same time they were about 8-fold lower than those reported in serum [31].…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…The levels of endoglin obtained with the commercial ELISA kit were greater than those reported by Li [16], who used an indirect sandwich ELISA kit. At the same time they were about 8-fold lower than those reported in serum [31].…”
Section: Resultscontrasting
confidence: 69%
“…The number of endoglin-positive vessels was significantly associated with a decreased rate of overall survival [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported in this study that angiogenesis was found to be activated in midstage lesions before the appearance of full-blown tumors suggesting that the formation of new blood vessels is essential for Clonal Expansion and formation of macroscopic tumors (Hanahan and Weinberg, 2000). But in the macroscopic tumor, the main factor affecting the density of blood vessels is the metabolic needs of tumor cells which usually increase with tumor progression (Sharma et al, 2005) Thus, in malignant tumors with severe invasiveness and progression, metabolic needs and consequently the development of blood vessels increases (Romani et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CD105 is a transforming growth factor beta (TGF-β) binding receptor preferentially expressed on endothelial cells (ECs) of all angiogenic tissues, including tumors, but weakly or not at all with those of normal tissues (Marioni et al, 2006) giving it the superiority as a marker with a greater specificity for tumor-induced angiogenesis. Moreover, its expression increased in the same time with the neo-angiogenic progression (Romani et al, 2006).…”
mentioning
confidence: 85%